2010
DOI: 10.1158/1940-6207.capr-09-0176
|View full text |Cite
|
Sign up to set email alerts
|

Null Activity of Selenium and Vitamin E as Cancer Chemopreventive Agents in the Rat Prostate

Abstract: To evaluate the potential efficacy of selenium and vitamin E as inhibitors of prostate carcinogenesis, four chemoprevention studies using a common protocol were done in a rat model of androgen-dependent prostate cancer. After stimulation of prostate epithelial cell proliferation by a sequential regimen of cyproterone acetate followed by testosterone propionate, male Wistar-Unilever rats received a single i.v. injection of N-methyl-N-nitrosourea (MNU) followed by chronic androgen stimulation via subcutaneous im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 40 publications
4
41
0
Order By: Relevance
“…Recent studies have noted an inverse relationship between selenium status and cancer risk in several tissues, including the esophagus, stomach, lung, and prostate [11]. McCormick et al [12] did not support the hypotheses that selenium is potent cancer chemopreventive agent in the prostate of rat. Liao et al [13] reported that selenium played a beneficial role for prevention of cisplatin hepatotoxicity in mice.…”
Section: Introductionmentioning
confidence: 96%
“…Recent studies have noted an inverse relationship between selenium status and cancer risk in several tissues, including the esophagus, stomach, lung, and prostate [11]. McCormick et al [12] did not support the hypotheses that selenium is potent cancer chemopreventive agent in the prostate of rat. Liao et al [13] reported that selenium played a beneficial role for prevention of cisplatin hepatotoxicity in mice.…”
Section: Introductionmentioning
confidence: 96%
“…Selenomethionine and selenized yeast were also negative in studies with rat models of prostate cancer [60, 61]. In one of these studies, α-tocopherol increased the incidence of prostate cancer, similar to the results of SELECT [60]. We found that selenium at physiological concentrations increased cell proliferation in LNCaP prostate cancer cells in vitro, but inhibited proliferation at higher doses [62].…”
Section: Chemopreventionmentioning
confidence: 59%
“…Selenomethionine did not affect risk of progression to prostate cancer in men with high grade prostatic intraepithelial neoplasia (PIN) [58] and selenized yeast did not affect risk in men with elevated PSA or other high risk indicators who were negative on biopsy [59]. Selenomethionine and selenized yeast were also negative in studies with rat models of prostate cancer [60, 61]. In one of these studies, α-tocopherol increased the incidence of prostate cancer, similar to the results of SELECT [60].…”
Section: Chemopreventionmentioning
confidence: 99%
“…For the former category, a couple of studies conducted in the late 1990’s before SELECT did not find any efficacy of SeMet and α-tocopheryl acetate alone or in combination or of Se-yeast on a prostate carcinogenesis model in rats. These negative results were initially communicated in meeting proceedings and the full results were only published after SELECT results had been published (38) (39). In one study, the potential of SeMet and α-tocopheryl acetate was examined to modulate PCa development in testosterone plus estradiol-treated Noble (NBL/Crl) rats, a model that involves sex hormone-induced oxidative stress and prostatic inflammation (39).…”
Section: Lessons From Major Clinical Trials That Failed To Validatmentioning
confidence: 99%